Mechanisms of carding - Lee, M (University of Oxford;Mathematical Institute, 1997)
A model for a slender thread or fibre in a slow viscous incompressible fluid is derived. The material of the thread is assumed to have no bending stiffness and to be strictly inextensible. The model is then applied to a simplified industrial situation found in carding, where a thread hangs off a hook. In two limiting cases, perturbation methods give approximate asymptotic solutions, and numerical solutions are found for the general case.